KONTROVERSI JIDAT HITAM DI MADURA: Studi Penafsiran Komparatif-Sektarian QS. al-Fatá¸¥ [48]: 29 - Zamzami, Mohammad Subhan (Fakulta Ushuluddin dan Humaniora Universitas Islam Negeri Walisongo Semarang, Indonesia, 2018)
This paper reveals athar al-sujÅ«dâ€™s interpretation in QS. al-Fatá¸¥ [48]: 29 behind the controversy of the stigma of black foreheads against certain groups in Islam. This paper is a result of literature and fieldwork research based on comparative interpretation methods (tafsÄ«r muqÄrin) on five tafsÄ«r books from different schools and interviews with some figures from different religious organizations in Madura. This research has discovered that the controversy from the stigma of a black forehead was not only triggered by different interpretations of athar al-sujÅ«d in QS. al-Fatá¸¥ [48]: 29, but also by several hadiths narrated by Aá¸¥mad, al-BayhaqÄ«, and al-BukhÄrÄ«, which cause controversy among Muslims in Madura. In fact, no group in Islam wants such controversy, either as the subject of the accuser or the accused as a group of black foreheads.